2008
DOI: 10.1111/j.1600-0722.2008.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human saliva substitutes in an erosion–abrasion cycling model

Abstract: Saliva may affect dental erosion-abrasion by reducing demineralization, enhancing remineralization, and acting as lubricant. This study tested the effect of human saliva substitutes in an erosion-abrasion cycling model designed for enamel and root dentin. Specimens were randomly assigned into the following groups (n = 8): artificial saliva (AS), artificial saliva + mucin (AS+M), deionized water (DIW, negative control), and pooled human saliva (HS, clinical reference). Each group was submitted to a cycle of 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 34 publications
4
58
1
17
Order By: Relevance
“…23 In the literature, there are few studies that test the action of pediatric medicines on teeth under conditions that mimic the oral cavity. 9,10,19 In our study, we observed that the pH values of pediatric medicines at room temperature were lower than at cold temperature, and that Claritin ® and Alivium ® presented the lowest pH values.…”
Section: 20mentioning
confidence: 99%
“…23 In the literature, there are few studies that test the action of pediatric medicines on teeth under conditions that mimic the oral cavity. 9,10,19 In our study, we observed that the pH values of pediatric medicines at room temperature were lower than at cold temperature, and that Claritin ® and Alivium ® presented the lowest pH values.…”
Section: 20mentioning
confidence: 99%
“…To clarify the effect of the human saliva on the reflection signals in group 2, the measurement results were compared with the ones obtained in group 4, where enamel samples were incubated in the mineral solution containing no proteins but similar pH and Ca∕P ratio as applied human saliva. The term "remineralization" is used here based on the published reports about the remineralizing effect of human saliva 49,50 and artificial saliva, 51,52 a solution containing different mineral salts (Ca 2þ , Mg 2þ , K þ , phosphates, buffers), 51 and sometimes also mucin or caboxymethylcellulose.…”
Section: Optical Erosion Analysis In Enamel Samplesmentioning
confidence: 99%
“…No sentido de se estabelecer um parâmetro na utilização da saliva nas pesquisas de erosão e abrasão "in vitro", foi testado o potencial remineralizador de uma saliva artificial (AS), saliva artificial + mucina (AS+M), saliva humana (HS, referência clínica) e água deionizada (controle negativo) no esmalte dental, com a imersão dos espécimes em 15 mililitro (ml) de ácido cítrico 1% pH 3,75 por 5 minutos, imersão em saliva por 30 minutos e escovação (500 ciclos com carga de 200 gramas) com dentifrício fluoretado (1.100 ppm de fluoreto de sódio-NaF). O desgaste do esmalte aumentou na seguinte ordem: AS, AS+M, HS e controle; a AS+M não diferiu da HS, concluindo-se que as salivas artificiais, principalmente a AS+M podem ser usadas nos experimentos "in vitro" no esmalte em substituição à saliva humana (Hara et al, 2008).…”
Section: Estrutura Dentalunclassified
“…Na perfilometria de contato, a superfície é escaneada com uma caneta com ponta de aço ou diamante, que penetra na superfície erosionada e pode superestimar a profundidade da lesão (Barbosa et al, 2012;Heurich et al, 2010). A perfilometria de não contato usa uma sonda de luz laser (branca ou azul clara), podendo analisar erosões profundas ou superfícies naturais curvadas, entretanto para se obter máxima sensibilidade e precisão são necessárias superfícies planas (Ablal et al, 2009;Rees, 2004;Elton et al, 2009;Hara et al, 2008;Schlueter et al, 2011;Venasakulchai et al, 2010;White et al, 2011;White et al, 2010).…”
Section: Métodos Quantitativosunclassified
See 1 more Smart Citation